Electrocardiogram Characteristics and Prognostic Value in Light-Chain Amyloidosis: A Comparison With Cardiac Magnetic Resonance Imaging - Guo, Xinli; Chen, Zhian; Wan, Ke; Song, Rizhen; Yang, Tingjie; Xu, Yuanwei; Zhang, Qing; Alexander, Kevin Michael; Han, Yuchi; Chen, Yucheng (Frontiers in Cardiovascular Medicine, 2021)
Background: An electrocardiogram (ECG) is a simple and cheap non-invasive tool that shows various abnormalities and has prognostic value for patients with light-chain amyloidosis (AL). The present study aimed to explore the association between ECG characteristics and cardiac magnetic resonance (CMR)-detected amyloid burden and to investigate the prognostic value of ECG in AL amyloidosis. Methods: We prospectively enrolled 99 patients with AL amyloidosis (56 male patients; median age, 58 y). Detailed clinical information, 12-lead ECG, and CMR data were collected. All patients were followed-up longitudinally and the endpoint was all-cause mortality. ECG characteristics were analyzed and correlated with the degree of late gadolinium enhancement (LGE) and extracellular volume (ECV) by T1 mapping on CMR. The prognostic value of ECG characteristics was analyzed using Kaplan–Meier survival analysis and multivariate Cox regression. Results: During a median follow-up period of 33 months, 69 of the 99 patients died. Fragmented Q wave-R wave-S wave (QRS), pathological Q waves, the Sokolow index, QRS duration, and voltages were significantly associated with the extent of LGE, native T1, and ECV by CMR (p < 0.05). Fragmented QRS and Sokolow index showed independent prognostic value in AL amyloidosis (p = 0.001; p = 0.026, respectively). Fragmented QRS remained independent after adjusting for clinical values (hazard ratio: 2.034; 95% confidence interval: 1.148–3.603; p = 0.015). However, no ECG characteristics were independent predictors for prognosis in AL amyloidosis when LGE and ECV were included in the multivariate analysis. Conclusion: ECG abnormalities showed significant association with CMR indicators of amyloid burden. Fragmented QRS has an independent prognostic value in AL amyloidosis and could be used as an alternative marker when CMR is not available.